Analisis Faktor-Faktor yang Mempengaruhi Pendapatan Usaha Tani Perkebunan Kopi Arabika di Distrik Welesi Kabupaten Jayawijaya - Semuel Pongmakamba’ La’lang; Hasan Basri Umar (Universitas Cenderawasih, 2025)
This study aims to examine and analyze the influence of price, total production, coffee processing technology, labor, capital, and land area on the income of Arabica coffee farmers in Welesi District, Jayawijaya Regency. This research employed a quantitative method with a survey approach. The population of this study was all coffee farmers in Welesi District totaling 100 people, and the sample was selected using probability sampling technique. Data were collected through questionnaires measured using a Likert scale and direct interviews. The data analysis methods used were classical assumption tests (normality, multicollinearity, and heteroscedasticity), multiple linear regression analysis, partial t-test, simultaneous F-test, and coefficient of determination R² test. The results showed that partially, price and total production variables had a positive and significant effect on coffee farmers' income at the 95 percent confidence level, while coffee processing technology, labor, and capital variables were only significant at the 90 percent confidence level. The land area variable had no significant effect on coffee farmers' income at both confidence levels. However, simultaneously, all six independent variables had a very significant effect on coffee farmers' income with a coefficient of determination value of 87.9 percent, while the remaining was influenced by other variables outside the research model. Keywords: Price, production, technology, labor, capital, land area, coffee farmers' income